2013
DOI: 10.2174/1574891x113089990032
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of a New Docosahexaenoic Acid Monoacylglyceride in Lung Adenocarcinoma

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Despite advances in research, diagnosis and treatment, lung cancer remains a highly lethal disease, often diagnosed at advanced stages and with a very poor prognosis. Therefore, new strategies for the prevention and treatment of lung cancer are urgently needed. The aim of the present study was to determine the anti-tumorigenic effects of docosahexaenoic acid monoacylglyceride (MAG-DHA), a newly patented DHA derivative in lung adenocarcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Western blots using specific antibodies against EGFR, ERK1/2, β-actin and phosphorylated forms of EGFR and ERK1/2 (all from New England BioLabs, Pickering, ON, Canada) were performed on cell lysate fractions as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blots using specific antibodies against EGFR, ERK1/2, β-actin and phosphorylated forms of EGFR and ERK1/2 (all from New England BioLabs, Pickering, ON, Canada) were performed on cell lysate fractions as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
“…shown that omega-3 PUFA supplementation prevent or reduce the growth of tumor cells (2,3,(5)(6)(7)(8). Moreover, clinical studies have demonstrated significant protective effects of omega-3 fatty acids against lung cancer and high omega-3 intake was associated with a lower risk of lung cancer (3,4,21).…”
Section: Mag-dha and Cbt Reduced Proliferation And Invasiveness Of Lumentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the present study was thus to evaluate the effects of MAG-DPA on pulmonary inflammation and remodeling occurring in PH. Fatty acids in monoacylglyceride form are generally recognized as safe and are widely used as emulsifying agents in the food industry (40). Moreover, PUFA monoacylglycerides have been demonstrated to increase the oral bioavailability of PUFA compared with commercially available marine oil (15,16,40).…”
mentioning
confidence: 99%
“…Fatty acids in monoacylglyceride form are generally recognized as safe and are widely used as emulsifying agents in the food industry (40). Moreover, PUFA monoacylglycerides have been demonstrated to increase the oral bioavailability of PUFA compared with commercially available marine oil (15,16,40). For the purposes of this study, an in vivo model of PH induced by monocrotaline (MCT) was used as experimental setting.…”
mentioning
confidence: 99%